Simulium (Psilopelmia) virescens, a new black-fly species (Diptera: Simuliidae) from the southwestern region of the state of Bahia, Brazil - Neusa Hamada; Nayra Gomes da Silva; Eleny da Silva Pereira (Memorias do Instituto Oswaldo Cruz, 2012)
The last-instar larva, pupa, male and female of Simulium virescens sp. nov. are described and illustrated. This species has a peculiar larva, which has an elongated head capsule and light-green colour. The first thoracic segment has tubercle on its dorsal region and the third thoracic segment has one pair of tubercles; the first to the fourth abdominal segments have one pair of tubercles on each segment. Until now this new species had only been collected at the type locality, which is on the middle stretch of the Correntina River in the southwestern portion of the state of Bahia, Brazil. Females were voraciously biting humans during the field work. This new species represents the second species of Simulium(Psilopelmia) in Brazil and the first registered outside of the Brazilian Amazon Region.